Influence of Amlodipine on Haemostatic Measurements during Clopidogrel Treatment in Patients with Coronary Artery Disease - Koh, Jin-Sin; Park, Yongwhi; Ahn, Jong-Hwa; Kang, Min Gyu; Kim, Kye-Hwan; Bae, Jae Seok; Park, Hyun Woong; Jang, Jeong Yoon; Park, Jeong Rang; Hwang, Seok-Jae; Kwak, Choong Hwan; Hwang, Jin-Yong; Tantry, Udaya S.; Gurbel, Paul A.; Jeong, Young-Hoon (Thrombosis and Haemostasis, 2019)
Amlodipine has a potential to reduce clopidogrel bioactivation through the cytochrome P450 3A4 enzyme in vivo, but the clinical impact of this interaction remains controversial. This randomized, open-label, two-period, crossover study was performed to evaluate the influence of amlodipine on the haemostatic profiles of high-risk patients during clopidogrel treatment. We recruited 40 Asian patients (Male/Female: n = 36/4) receiving clopidogrel (75 mg/day), aspirin (100 mg/day) and rosuvastatin for at least 6 months following percutaneous coronary intervention. Patients were randomly assigned to receive either 5 mg daily amlodipine or not for 2 weeks, and then were crossed over to the other treatment for 2 weeks. Haemostatic measurements were conducted with the VerifyNow assay and thromboelastography (TEG). Primary endpoint was P2Y12 Reaction Units (PRU) during on- versus off-amlodipine treatment. The on-amlodipine strategy showed higher level of PRU compared with the off-amlodipine strategy (176.8 ± 75.4 vs. 150.7 ± 65.5 PRU; ∆mean: 26.1 PRU; ∆95% confidence interval [CI]: 4.5–47.7 PRU; p = 0.019). Platelet-fibrin clot strength measured by TEG was lower during on- versus off-amlodipine treatment (7,712 ± 1,889 vs. 8,559 ± 2,174 dyne/cm2; ∆mean: –847 dyne/cm2; ∆95% CI: –1,632 to –62 dyne/cm2; p = 0.035). After amlodipine discontinuation, 27 patients (67.5%) showed a decrease in PRU, which was associated with ‘PRU ≥ 160 on-amlodipine’ in multivariate analysis (odds ratio: 62.014; 95% CI: 2.302–1670.328; p = 0.014). In conclusion, amlodipine increases platelet reactivity and decreases platelet-fibrin clot strength during clopidogrel treatment. In addition, the effect of amlodipine discontinuation on clopidogrel responsiveness is associated with on-amlodipine platelet reactivity.
Keywords: amlodipine; clopidogrel; platelet; clot